E-Marketing Usage As An Increase In Competitive Advantage Through Product Innovation And Marketing Performance (Survey On MSMEs In Central Java) - Muh. Nur Luthfi Aziz; Puji Nurhayati; Aji Yudha; Nenden Nur Annisa (Journal of Business and Management Review, 2022)
MSMEs are the most important pillar of the Indonesian economy. MSMEs have a very significant contribution to the national economy (GDP). MSMEs also have an important role in advancing the regional economy to make MSMEs conduct the increasingly competitive business competition. This requires every MSME to have its advantages to compete in the global world. This research aims to test the influence of e-marketing usage on competitive advantage through product innovation and marketing performance. The sampling technique uses purposive sampling with a sample of 347 MSMEs in Central Java. Data analysis techniques use path analysis with Warp PLS 5.0 software. The results showed that e-marketing usage has a positive and significant effect on product innovation and competitive advantage, and e-marketing usage has a positive and significant effect on competitive advantage through product innovation. However, e-marketing usage does not affect marketing performance and e-marketing usage does not affect competitive advantage through product innovation.